Challenges impeding South African municipalities from adopting waste-to-energy schemes : an exploratory approach - Mutezo, Gamuchirai Thelma (Energy Research Centre, 2016)
As a resource, waste is abundantly available but largely underexploited in South Africa. Through waste to energy transformation, waste offers a variety of benefits that could address socio-economic and environmental challenges such as energy poverty, decreasing landfill space and greenhouse gas (GHG) emissions. As South Africa becomes more urbanised, the urban population will rapidly increase and greater effort will be required to manage waste and provide energy services. Municipalities have the potential to deal with these challenges and realise many benefits by transforming and valorising waste through waste-to-energy (WtE) schemes. The most prevalent WtE technologies include biological (biochemical conversion) and thermal (thermo-chemical) based conversion technologies. Biological technologies mainly employ anaerobic digestion (AD) of waste to produce biogas which can be used directly or upgraded to other secondary energy carriers. Landfill gas recovery is also based on anaerobic breakdown of waste in landfills. Thermal treatment methods that produce heat and electricity include combustion, gasification, and pyrolysis. The most common form of WtE conversion technology is combustion or incineration of solid waste. In the developing world, AD is the most common technology especially for small scale and domestic applications. WtE technologies have been successfully deployed in many developed as well as some developing countries but there are limited initiatives in South Africa due to a number of barriers to the deployment of the technology. This study explored the barriers to wide scale deployment of WtE technologies in South Africa with a specific focus on adoption challenges faced by local municipalities specifically in the Western Cape Province. Four objectives were identified, namely: (1) investigate existing waste management methods, challenges experienced and current (proposed) interventions; (2) investigate local municipalities' efforts to implementing WtE schemes and the challenges encountered; (3) estimate the amount of energy that can be produced by local municipalities from waste and the extent to which the energy gap could be narrowed and; (4) identify the most appropriate WtE technology that local municipalities could implement. The research methodology comprised of a mixed methods approach which encompassed both qualitative and quantitative approaches, based on an exploratory design. A sample of five municipalities was identified and participated, from a population of 24 municipalities in the Western Cape Province. The criteria used to select the municipalities include (1) experiences, plans and efforts to adopt WtE (2) socio-demographic trends such as population growth and urbanisation rates as well as (3) proximity and ease of collecting data physically. Some challenges that were experienced relate to limited availability and accuracy of waste generation data and waste compositions, limited availability of municipal documents (such as feasibility studies and policy documents) and the inability of participants to answer all the relevant questions. The latter was mainly due to the different stages of WtE implementation in the different municipalities. Through the analysis, it was noted that socio-demographic trends such as population growth and in-migration increased between the 2001 and 2011 period, which also indicated an increase in the waste generated. Although local municipalities were implementing waste initiatives such as recycling and composting, none had physically implemented any WtE schemes. However, the municipalities were exploring the technologies and were at different stages, mainly at the feasibility stage. The challenges deterring municipalities from adopting WtE include: 1. Unsuitable waste feedstock for energy generation and poor data on waste generation and composition for investment decision making, 2. Restrictions on independent power producers (IPPs) of electricity to directly supply power to municipalities as well as timeous wheeling agreements (the monopoly of Eskom) 3. Poor synchronisation of policies (energy and waste policies do not provide a solid platform for establishing WtE industries), 4. Poor integration of WtE into waste management planning, 5. Limited knowledge of technologies by decision makers and lack of political will; 6. Low landfill tariffs, 7. Limited access to capital to invest in technologies and high investment costs depending on the type of technology, 8. Lack of skills to implement technologies, 9. Limited awareness of the technologies and their benefits and opposition from the public for various reasons including emissions of hazardous gases, and 10. Delays in processing environmental and legal applications.